DAMPAK PENGGUNAAN GADGET PADA SIKAP SOSIAL SISWA SEKOLAH DASAR : STUDI LITERATUR - Salsabila Maghfirah Ramadhani; Elfia Sukma; Inggria Kharisma (STKIP Subang, 2026)
In today's digital age, devices such as smartphones and tablets have become essential to the daily lives of elementary school children. This, in turn, has a number of significant consequences for their social development, including both positive and more serious negative effects. This study aims to conduct an in-depth analysis of these influences by applying a comprehensive literature review approach, compiling and analyzing findings from relevant, recent scientific journals. The method used was a rigorous systematic literature review, drawing on sources from accredited journals published between 2018 and 2025, with a primary focus on empirical research in Indonesia. The analysis revealed that negative impacts were more pronounced, such as a decline in the quality of direct social relationships, the emergence of antisocial behavior, and a reduced capacity for empathy among students. Meanwhile, the observed positive effects were limited to increased creativity through digital communication and better access to information. Overall, the study's conclusions emphasize the need for close supervision by parents and educators to mitigate potential risks and provide practical advice on limiting daily gadget use within safe limits.